If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 + 2x = -5 Solving -6 + 2x = -5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 2x = -5 + 6 Combine like terms: -6 + 6 = 0 0 + 2x = -5 + 6 2x = -5 + 6 Combine like terms: -5 + 6 = 1 2x = 1 Divide each side by '2'. x = 0.5 Simplifying x = 0.5
| y=3x^2+13x+4 | | 20-7y=6y-6 | | d=56t | | 3+7x=6x+9 | | 48=12r | | 8-s=3+4t | | -2x+1=4x-1 | | 116.2396354x^2+3332.382299x+23564.48=0 | | -6x+9+5x=0 | | 9x+5-4x+3= | | 126x^6-63x^5-35x^4=0 | | 6(3x-5)-7x=8 | | 8x+2y=0 | | -2a+32=2 | | .35x+500=2.50x | | 5t^2+10t=-33 | | 2.45-3.1x=21.05 | | 2(5x-2)2+5=25 | | 12345678900+0987654321= | | 4(.5-w)=-18 | | 3[2]+[2]m=102 | | 2x+x-15=180 | | |4n-5|=18 | | -7+3n=-(2+2n) | | .35x+500=250x | | 6(3x-5)=8 | | x-0.1x+0.0(x-0.1x)=70.79 | | 3(2x-1)-(4-x)=5x-13 | | 7x+6x-3x-45=15x | | 5-5h=2-8h | | 4.9t^2+10t=-33 | | (7x+1)(19x-3)= |